Aspirational laws: performative governance in Mongolia's fang feng (Saposhnikovia divaricata) trade for the TCM market - Waters, Hedwig Amelia (Frontiers in Human Dynamics, 2025)
Since Mongolia's transition from socialism in 1991, wild medicinal plants have been harvested from public lands and exported to diverse Asian medicinal markets. This article examines how the post-socialist, market-democratic state has struggled both to regulate the illegal outflow of wild flora and to build a national development industry around cultivated medicinal plants using the instruments of law, techno-science, and research. These competing trade dynamics are explored through the case of fang feng (Saposhnikovia divaricata), a plant popularly used in Traditional Chinese Medicine (TCM) to treat Covid-19. Wild fang feng, prized for its high metabolic content, is especially lucrative on global markets, fueling a robust gray economy in Mongolia. In response, the Mongolian government—along with its network of industrial, political, and academic consultants—has produced a series of “aspirational laws”: frameworks imbued with the hope that their presence will eventually bring national development dreams into being. Although often unrealizable or unenforceable in practice, these laws serve other functions, as explored in the anthropology of the nation-state and economic performativity: they simplify a complex, fragmented market to a narrative of techno-scientific progress, projecting an image of active governance while creating pathways for elite financial gain. This interplay between aspirational regulation and gray economy continues to shape the moral and material terrain of Mongolia's export-oriented medicinal plant trade.